Examining bi-directionality between Fear of Missing Out and problematic smartphone use. A two-wave panel study among adolescents. (July 2020) - Lo Coco, Gianluca; Salerno, Laura; Franchina, Vittoria; La Tona, Antonino; Di Blasi, Maria; Giordano, Cecilia
Highlights: A two-wave cross-lagged panel design was tested with 242 adolescents. FoMO and problematic smartphone use (PSU) were related at cross-sectional level. No cross-lagged associations between FoMO and PSU were longitudinally supported. Causal links between FoMO and PSU need to be examined across different time lags. Abstract: Background: In recent years, the Fear of Missing Out (FoMO) construct has been the object of growing attention in digital technology research with previous studies finding support for the relationship between FoMO and problematic smartphone use (PSU) among adolescents and young adults. However, no previous studies clarified the causal link between FoMO and PSU using a longitudinal design. Methods: An auto-regressive, cross-lagged panel design was tested by using a longitudinal dataset with two waves of data collection (T0 and T1, one year apart). Participants included two hundred and forty-two adolescents (109 males and 133 females), with a mean age of 14.16 years, who filled out the Fear of Missing Out scale (FoMOs) and the Smartphone Addiction Scale (SAS). Moreover, participants filled out the Difficulties in Emotion Regulation Scale (DERS), at the first time-point of data collection. Results: The findings of the study show that FoMO (both FoMO-Fear and FoMO-Control subscales) and PSU are positively related at both time-points (i.e. at a cross-sectional level). However no cross-lagged associations between them were longitudinally supported. Females and older adolescents show higher FoMO-Fear at T1. Conclusions: The findings of the present study suggest caution when causal links between FoMO and PSU are inferred.